Immune activation by DNA damage predicts response to chemotherapy and survival in oesophageal adenocarcinoma - Turkington, RC; Knight, LA; Blayney, JK; Secrier, M; Douglas, R; Parkes, EE; Sutton, EK; Stevenson, L; McManus, D; Halliday, S; McCavigan, AM; Logan, GE; et al. (BMJ Publishing Group, 2019)
Objective: Current strategies to guide selection of neoadjuvant therapy in oesophageal adenocarcinoma (OAC) are inadequate. We assessed the ability of a DNA damage immune response (DDIR) assay to predict response following neoadjuvant chemotherapy in OAC.